Review the status of alleged online insult cases: Rais - Daily Express, (KK) (Daily Express (kk), 2011)
JELEBU : Information Communication and Culture Minister Datuk Seri Dr Rais Yatim on Monday asked the Attorney-General's Chambers to review the status of cases of alleged online insult of Islam and Malay culture on which no action had been taken.